2011
DOI: 10.1063/1.3646491
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic characterization of Co-NiO-Ni core-shell nanotube arrays

Abstract: Well-aligned Ni and Co-NiO-Ni core-shell nanotube arrays with an average outer diameter of about 200 nm have been synthesized in a porous anodic aluminum oxide (AAO) template by the direct electro-deposition method. The result shows that the nanotubes were polycrystalline phase. Angular dependent coercivity Hc(θ) indicates that the magnetization reversal mechanisms are mainly dominated by the “curling mode” for Ni nanotubes, while a transition from curling to transverse is observed in Co-NiO-Ni core-shell nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…2b). Such increase at low temperature has also been found in previous studies of ferromagnetic Co-NiO-Ni nanotube [28], which further indicated that our samples show ferromagnetism. Fig.…”
Section: Resultssupporting
confidence: 80%
“…2b). Such increase at low temperature has also been found in previous studies of ferromagnetic Co-NiO-Ni nanotube [28], which further indicated that our samples show ferromagnetism. Fig.…”
Section: Resultssupporting
confidence: 80%
“…Magnetic nanorods of 100–200 nm diameter can be covered with polymers to prevent their agglomeration . One can generate Ni, Co, permalloy, and other metallic nanorods and nanotubes . As an example, the Scanning Electron Microscope (SEM) image shown in Figure shows nickel and cobalt nanorods produced in our laboratory.…”
Section: Nanorod Synthesismentioning
confidence: 99%
“…This behavior is favorable for easy alignment of magnetic nanorods during formation of thin coating films. Magnetic behavior of nanotubes is more complex and the methods of their processing for magnetic nanocomposites requires further investigation.…”
Section: Nanorod Synthesismentioning
confidence: 99%
“…From the FORC diagrams, one can extract the profiles of the magnetic interactions and coercivity distributions (Proenca et al, 2013b). On the other hand, due to the empty inner core of the NTs, a different magnetization distribution is created (Landeros et al, 2007Chen et al, 2011b), which is mainly allocated parallel to the tube axis, thus leading to the canting of the spins near the tube ends (Proenca et al, 2013c). When comparing several Co nanostructured arrays (high-aspect-ratio NWs and NTs, small-aspect-ratio nanopillars, and thin film nanohole arrays), the highest magnetostatic interactions were found to occur for the NWs case (Figure 24.20a;Proenca et al, 2013c).…”
Section: Interactionsmentioning
confidence: 99%